Corak Ghinâ’ dalam Membaca Alquran (Studi Historis terhadap Perkembangan Variasi Lagu Alquran Syaikh al-Qurrâ’ Azra’i Abdurrauf) - Wanto, Sugeng; Nasution, Muhammad Roihan; Tanjung, Hadi Gunawan (Universitas Islam Negeri Sumatera Utara, 2020)
Fast traslateABSTRACTSheikh Azra'i Abdurrauf is Shaykh al-Qurrâ’ from North Sumatra who mastered the sciences of the Qur’an such as tajwîd, fashâhah, interpretation, qirâ'at and ghinâ'. However, his character and role is not seen in historical records and tends to disappear with his death. Therefore, the authors considers it important to write a study with the title